The role of mid‐tropospheric moistening and land‐surface wetting in the progression of the 2016 Indian monsoon. (18th November 2021) - Menon, Arathy; Turner, Andrew G.; Volonté, Ambrogio; Taylor, Christopher M.; Webster, Stuart; Martin, Gill
Abstract: Accurately predicting the Indian monsoon is limited by inadequate understanding of the underlying processes, which feed into systematic model biases. Here we aim to understand the dynamic and thermodynamic features associated with the progression of the monsoon, using 2016 as a representative year, with the help of convection‐permitting simulations of the Met Office Unified Model. Simulations are carried out in a 4 km resolution limited‐area model, nested within a coarser global model. Two major processes thought to influence the northwestward progression of the monsoon are: (a) the interaction between the low‐level monsoon flow and a mid‐tropospheric dry‐air intrusion from the northwest, and (b) land–atmosphere interactions. We find that the 4 km limited‐area model simulates the mid‐tropospheric moistening that erodes the northwesterly dry intrusion, pushing the northern limit of moist convection northwestwards. The surface soil moisture also plays a major role at the leading edge of the monsoon progression. The heavy rains associated with the local onset wet the soil, reducing the sensitivity of surface fluxes to soil moisture and weakening the land influence on further progression of monsoon rains. The 4 km model is tested with an alternative land‐surface configuration to explore its sensitivity to land‐surface processes. We find that the choice of soil and vegetation ancillaries affects the time‐scales of soil moisture–precipitation feedback and the timing of diurnal convection, thereby affecting the local onset. We further compare these simulations with a parametrized convection run at 17 km resolution to isolate the effects of convective parametrization and resolution. The model with explicit convection better simulates the dynamic and thermodynamic features associated with the progression of the monsoon. Abstract : Time evolution of (a) 3‐day mean rainfall (blue lines), and the spatial correlation between 3‐day antecedent rains and 0630 UTC (1200 IST) evaporative fraction (red lines), and (b) area‐mean sensible heat flux ( H, red lines) and spatial standard deviation of the sensible heat flux (blue lines) from the two 4 km simulations with IGBP and CCI land ancillaries at 0630 UTC (1200 IST) over the monsoon core zone. The grey vertical lines separate the months May, June and July.